2013
DOI: 10.1103/physrevlett.110.018307
|View full text |Cite
|
Sign up to set email alerts
|

Granular Convection in Microgravity

Abstract: We investigate the role of gravity on convection in a dense granular shear flow. Using a microgravity-modified Taylor-Couette shear cell under the conditions of parabolic flight microgravity, we demonstrate experimentally that secondary, convective-like flows in a sheared granular material are close to zero in microgravity and enhanced under high-gravity conditions, though the primary flow fields are unaffected by gravity. We suggest that gravity tunes the frictional particle-particle and particle-wall interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Another related issue that remains untouched is the effect of particle softness and external compression (gravity here) on the non-locality. A study of effect of pressure (gravity) on primary and secondary velocity fields, as done recently in [73,74], also deserves a further study, as well as the effect of softness and pressure on the shear banding. Looking towards the future, we are now in a position to address various important issues, such as unexpectedly high shear strength of the material at low (normal) stress or reduced gravity and a direct relation between the contact anisotropy and the shear strength of the material.…”
Section: Discussionmentioning
confidence: 90%
“…Another related issue that remains untouched is the effect of particle softness and external compression (gravity here) on the non-locality. A study of effect of pressure (gravity) on primary and secondary velocity fields, as done recently in [73,74], also deserves a further study, as well as the effect of softness and pressure on the shear banding. Looking towards the future, we are now in a position to address various important issues, such as unexpectedly high shear strength of the material at low (normal) stress or reduced gravity and a direct relation between the contact anisotropy and the shear strength of the material.…”
Section: Discussionmentioning
confidence: 90%
“…shear zone geometries [16][17][18], dilatancy and packing [19][20][21], segregation [22,23], alignment and orientational order [7,24,25], macroscopic viscosities [26,27] and secondary flows [1,28]. The latter was also reported for a slightly different Taylor-Couette geometry [29]. Wortel et al [1] described the following characteristic properties of elongated grains under shear in splitbottom containers: the material formed a heap in the central region, which reached a saturation height after some transient phase.…”
Section: Introductionmentioning
confidence: 89%
“…Murdoch et al (2013b,c,a) used a Taylor-Couette geometry and measured both sheared and convective flows induced by the shearing. Particularly, Murdoch et al (2013b) reported the effect of gravity to the sheared granular convection. They claimed that the gravity plays an essential role to make a stiff grains network in a bulk granular matter.…”
Section: Gravity Effect To the Granular Convective Velocitymentioning
confidence: 99%